IMPACT OF HAUSA LANGUAGE ON ENGLISH PROFICIENCY AMONG SECONDARY SCHOOL STUDENTS IN KANO STATE, NIGERIA - Omikunle, Sakiru Ayinde; Yusuf, Omoniyi Yusuf; Rabiu, Zulai Muhammed (African Journal of Social and Behavioural Sciences, 2025)
This study investigates the impact of the Hausa language on the English proficiency of secondary school students in Kano State, Nigeria. The research examines how interference from Hausa affects students' pronunciation, syntax, vocabulary, and overall fluency in English and identifies strategies employed by teachers to mitigate this interference. A mixed-methods approach was used, incorporating questionnaires and interviews with 100 teachers from selected schools. Descriptive and inferential statistical analyses revealed that Hausa significantly interferes with students' English proficiency, particularly in pronunciation and syntax, with many students relying heavily on Hausa linguistic structures. Teachers employed strategies such as encouraging English practice, targeted vocabulary instruction, and real-time error correction, which were found to be the most effective in improving proficiency. Code-switching was commonly used but had limited long-term effectiveness. Based on these findings, it is recommended that educational policies focus on enhancing English language exposure through structured practice, vocabulary development, and teacher training on bilingual education techniques. Future research should extend this inquiry to other regions and languages to further understand language interference and its implications for English language acquisition in Nigeria.